Semaphorin-3A, semaphorin-7A gene single nucleotide polymorphisms, and systemic lupus erythematosus susceptibility. (19th May 2019) - Liu, Li-Na; Wang, Peng; Zou, Yan-Feng; Xu, Zhiwei; Cheng, Jian; Zhang, Yuzhou; Hu, Wenbiao; Pan, Hai-Feng
Abstract: Background: Semaphorin-3A (Sema3A) and Semaphorin-7A (Sema7A) play crucial roles in immune system by inhibiting T cell proliferation and leading to the secretion of pro-inflammatory cytokines. Increasing evidence suggest that Sema3A and Sema7A may link to the development and pathogenesis of systemic lupus erythematosus( SLE). Objective: This study aims to evaluate the association of Sema3A, Sema7A gene single-nucleotide polymorphisms (SNPs) with susceptibility to SLE. Methods: There were 495 SLE patients and 493 healthy controls in the study. Sema3A gene and Sema7A gene were genotyped by improved multiple ligase detection reaction (iMLDR), their plasma expression levels were detected by enzyme-linked immunosorbent assay (ELISA). Results: No differences in genotype and allele frequencies of these SNPs were observed between SLE patients and healthy controls. However, analysing Sema3A and Sema7A SNPs with clinical manifestations of SLE indicated that, in Sema3A, the A allele frequencies of rs7804122 polymorphism was higher in patients with oral ulcers. In Sema7A, there were differences in allele frequencies of the rs2075589 and rs28362930 polymorphisms between SLE patients with haematological disorder and those without. The GG genotype and G allele frequencies of rs28362930 and the CC genotype, and C allele frequencies of rs741761 were both related to discoid rash in SLE patients. The allele frequency of G (rs28362930) was higher in SLE patients with renal disorder. There were differences in the genotype frequencies and allele frequencies of rs741761 between SLE patients with and without arthritis. No differences in plasma Sema3A and Sema7A levels were detected in SLE patients of different genotypes. Conclusions: Sema3A and Sema7A gene polymorphisms are not related to SLE genetic susceptibility, but may link to several clinical features of SLE.